THE EFFECT OF DIFFERENTIATED LEARNING STRATEGIES ON ENHANCEMENT OF PKN CONCEPTS IN STUDENTS IN CLASS IV PRIMARY SCHOOL / PENGARUH STRATEGI PEMBELAJARAN BERDIFERENSIASI TERHADAP PENINGKATAN PEMAHAMAN KONSEP PKN SISWA KELAS IV SEKOLAH DASAR - Nurlaela Sari, Siti; Arifuddin, Ahmad; Mudiyanto, Heru (Al-Mudarris: Journal Of Education, 2024)
The purpose of this study is to determine the effects of using differentiating teaching strategies on students' understanding of concept knowledge in PKN IV classrooms at SDN Pelandakan 2 Kota Cirebon. This study is a quantitative study using a pre-experimental design with a single group pretest-posttest layout. The techniques used for data collection are observation and testing techniques. On the other hand, the sample preparation technique uses purposive sampling with a sample size of about 20 participants. Furthermore, the data used in the analysis study includes observational data analysis, N-Gain, and non-parametric Wilcoxon hypothesis testing. The research results showed that the activity of teachers who used differentiation learning strategies when teaching PKN at the last meeting was in the very good category at 96%, and students' understanding of the PKN concept increased by 0.4091, which is included in the medium category. H0 is rejected and Ha is accepted, based on the results of non-parametric hypothesis testing with the Wilcoxon test, which shows that the significance value of 0.000 is smaller than 0.05. In class IV of SDN Pelandakan 2 Cirebon City, there was a significant relationship between the application of differentiation learning strategies and increasing students' understanding of PKN concepts regarding material unit 4 My Country, Indonesia.